Nonlinear heterogeneous dynamic substructuring and partitioned FETI time integration for the development of low‐discrepancy simulation models. (8th May 2017) - Bursi, Oreste S.; Abbiati, Giuseppe; Cazzador, Enrico; Pegon, Pierre; Molina, Francisco J.
Summary: This article presents a novel approach to model validation and to the calibration of complex structural systems, through the adoption of heterogeneous (numerical/physical) simulation based on dynamic substructuring (HDS). HDS isolates the physical sub‐system (PS) that contains the key region of nonlinear behavior of interest and is tested experimentally, separate from the remainder of the system, that is, the numerical sub‐system (NS), which is numerically simulated. A parallel partitioned time integrator based on the finite element tearing and interconnecting method plays a central role in solving the coupled system response, enabling a rigorous and stable synchronization between sub‐systems and a realistic interaction between PS and numerical sub‐system response. This feature enhances the quality of benchmarks for validation and calibration of low‐discrepancy models through virtual structural testing . As a proof of concept, we select an old reinforced concrete viaduct, subjected to seismic loading. Several HDS were conducted at the European Laboratory for Structural Assessment in Ispra (Italy) considering two physical piers and related concave sliding bearings as PSs of the heterogeneous system. As a result, the benefit of employing HDS to set benchmarks for model validation and calibration is highlighted, by developing low‐discrepancy FE models of critical viaduct components. Copyright © 2017 John Wiley & Sons, Ltd.